Motivation as an Mediation Variable in the Influence of Competence and Work Discipline on Employee Performance - Wijayanti, Feronika; Hadiyati, Ernani; Ahmad Ahmad (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study seeks to examine the influence of competence, work discipline, and motivation on employee performance. The study was conducted at the State Polytechnic of Malang, East Java, Indonesia with a sample of 208 contract employees. The reason for choosing this sample is because contract employees for performance assessment are regulated, assessed and evaluated by the leaders at the State Polytechnic of Malang. Unlike employees with civil servant status, who are assessed by the ministry. The data analysis method uses the Structural Equation Model (SEM) with Variance Based SEM with smartPLS 3.3.0 Software. Questionnaires distributed through Google Forms were used to collect the data. The study's outcomes show that both competence and work discipline play a significant role in shaping employee performance. Likewise, motivation succeeded in becoming an mediating factor for assessing the relationship between competence, work discipline, and employee performance, although its value was not greater than its direct influence. The data reveal that competence, work discipline and motivation remain considerations from time to time to achieve optimal employee performance.